The definition, production and validation of the direct vision standard (DVS) for HGVS. Final Report for TfL review - Steve Summerskill; Russell Marshall; Abby Paterson; Anthony Eland; James Lenard (2019)
This report presents research performed by Loughborough Design School (LDS) on behalf of Transport for London. The research has been conducted against a background of over representation of heavy goods vehicles (HGVs) being involved in road traffic accidents with vulnerable road users (VRUs) where ‘failed to look properly’ and ‘vehicle blind-spot’ are often reported as the main casual factors in the accident data. Previous work by LDS on driver’s vision from HGVs has identified the need to reduce reliance on indirect vision via mirrors through the specification of a direct vision standard (DVS) for HGVs. Recent work commissioned by TfL and performed by the Transport Research Laboratory (TRL) resulted in a draft DVS. This draft DVS has been evaluated and reworked by the LDS team to produce a viable and robust method to quantify direct vision performance of an HGV together with a means to rate that vision performance against a star rating standard. Throughout this process significant stakeholder consultation has been used to support the development of the DVS. A total of 27 vehicles representing the majority of the current Euro 6 N3 HGV fleet have been modelled in CAD. Where data were available these have been mounted at the highest, lowest and most sold heights to produce a sample of 54 test vehicles. A methodology has been developed that utilises volumetric projection of the field of view of the driver via the windows in the cab. This projection is then intersected with an assessment volume. The result is a volumetric representation of the space around a HGV cab that the driver can see to the front, driver and passenger sides. The volume of this space can be calculated to provide a rating of direct vision performance. An iterative design process was followed that explored different specifications of the assessment zone around the cab, factoring in the collision data with VRUs and the use of weightings to prioritise what needs to be seen. Two weighting schemes were evaluated one prioritising the volumes vertically, recognising the importance of being able to see closer to the ground, and a second prioritising the volumes directionally to address the prevalence of accidents being greater to the front and passenger side when compared to the driver’s side. The final specification of the volumetric assessment consists of a single, unweighted zone around the cab, informed by the current coverage of mirrors specified in UNECE regulation 46. This was done to foster direct vision that aims to remove the reliance on mirrors and thus should focus on providing direct vision of the areas currently covered by mirrors. The vehicle sample was then evaluated for its performance using this assessment, providing a volumetric score for each vehicle. These volumetric scores were then quantified by correlating them with a VRU simulation. Thirteen 5th %ile Italian female VRUs were placed around the vehicle and moved laterally to a point at which their head and shoulders could be seen. This served to provide context for the volumetric results such that a particular volume could be equated to an average distance at which the small adult could be seen. Furthermore, the VRU simulations provided a means to translate the volumetric performance into star ratings. Four star rating specifications were produced following an absolute (based on risk/safety) and a relative (based on the performance of the current fleet) approach. For both absolute and relative two iterations were proposed: 1. the VRU simulation distances were used to establish a threshold value, 2. the median volumetric result was used to establish a threshold value. The final option taken forwards used the VRU simulation distances for a 5th %ile Italian female to define the 1 star boundary. Vehicles able to provide direct vision of the VRUs at an average of